2015
DOI: 10.3992/jgb.10.2.113
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Change in Concrete Strength Due to Fabric Formwork

Abstract: Fabric, as a flexible formwork for concrete, gives builders, engineers, and architects the ability to form virtually any shape. This technique produces a superb concrete surface quality that requires no further touch up or finishing. Woven polyolefin fabrics are recommended for this application. The texture of this fabric allows water from concrete mix to bleed, and therefore reduces the water-cement ratio of the mix. Due to the reduction in the water-cement ratio, a higher compressive strength in fabric-forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
1
6
0
1
Order By: Relevance
“…Delijani (2010) demonstrated improvements in surface hardness for fabric-cast concrete and confirmed that permeable fabric formwork systems provide surface, rather than global, increases in strength. Chandler and Pedreschi (2007) qualitatively noted that concrete cast into a fabric mould gives a much improved surface finish ( Figure 3).…”
Section: Fabric Formworksupporting
confidence: 68%
“…Delijani (2010) demonstrated improvements in surface hardness for fabric-cast concrete and confirmed that permeable fabric formwork systems provide surface, rather than global, increases in strength. Chandler and Pedreschi (2007) qualitatively noted that concrete cast into a fabric mould gives a much improved surface finish ( Figure 3).…”
Section: Fabric Formworksupporting
confidence: 68%
“…The previous works performed on the pneumatic/vacuumatic formwork theme has been summarized in Table 5. 8. Durability, sustainability, efficiency and quality improvement Delijani (2010) and Delijani et al (2015) investigated and documented the changes in concrete quality and strength due to the use of woven polyolefin fabrics by two sets of tests. Variables in this study were types of fabric permeability and types of concrete.…”
Section: Form Findingmentioning
confidence: 99%
“… Filtering action of the fabric improves the surface finish and member durability (Lamberton 1989, Abdelgarder and El-Baden 2012, Delijani 2010. It also has several disadvantages including:  Relaxation can occur due to the prestress forces in the membrane.…”
Section: © Ascementioning
confidence: 99%